CMOS VLSI design : - Weste, Neil H. E. (Addison Wesley, 2011)
This extensively updated Fourth Edition covers the entire field of modern integrated circuit design, helping readers play effective roles in any contemporary CMOS VLSI project." "This text offers deep, practical coverage of delay, power, interconnect, robustness, SPICE, power consumption, VHDL/​Verilog and SystemVerilog, 65 nm design, and many other topics. The authors link theory to practice through hundreds of problems, worked examples, and exercises, and share their unsurpassed experience through war stories , Historical Perspective sections, and detailed guidance for avoiding design pitfalls." "For all engineers working in VLSI design, circuit design, logic design, and related fields.